1991
DOI: 10.2337/diab.40.11.1472
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Islet β-Cell Function After Hemipancreatectomy in Dogs

Abstract: The metabolic consequences of hemipancreatectomy in living pancreas donors were tested in a dog model in which a 50% lobe-specific pancreatectomy was performed. Removal of the dorsal lobe (analogous to a donor, n = 4) resulted in a progressive increase in fasting glucose during 12 mo from 5.32 +/- 0.16 to 8.17 +/- 0.28 mM and a decrease in fasting insulin from 54 +/- 3 to 6.0 +/- 2.4 pM and glucose clearance (Kg) from 3.00 +/- 0.22 to 1.00 +/- 0.06 mM. Removal of the ventral lobe (analogous to a recipient, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Presumably, there was only limited overall pancreas regeneration during the ϳ6 weeks between partial pancreatectomy and euthanasia in the current studies because the surgeon's estimate of the extent of pancreatic resection and the measured mass of pancreas remnant at euthanasia corresponded closely. Moreover, previous studies in dogs maintained for 12 months after ϳ50% pancreatectomy showed progressive hyperglycemia developing into diabetes (11). The current studies were not designed to examine ␤-cell regeneration but were focused on the impact of an acute decrement in ␤-cell mass on insulin secretion.…”
Section: Av Matveyenko Jd Veldhuis and Pc Butlermentioning
confidence: 99%
“…Presumably, there was only limited overall pancreas regeneration during the ϳ6 weeks between partial pancreatectomy and euthanasia in the current studies because the surgeon's estimate of the extent of pancreatic resection and the measured mass of pancreas remnant at euthanasia corresponded closely. Moreover, previous studies in dogs maintained for 12 months after ϳ50% pancreatectomy showed progressive hyperglycemia developing into diabetes (11). The current studies were not designed to examine ␤-cell regeneration but were focused on the impact of an acute decrement in ␤-cell mass on insulin secretion.…”
Section: Av Matveyenko Jd Veldhuis and Pc Butlermentioning
confidence: 99%
“…believe that our hypothesis cannot explain the "specific lesion" of loss of first phase insulin secretion. We find nothing particularly specific in this change since it is also seen prior to the onset of Type 1 (insulindependent) diabetes [13] and after partial pancreatectomy [14,15].…”
mentioning
confidence: 97%